2017
DOI: 10.5009/gnl15566
|View full text |Cite
|
Sign up to set email alerts
|

Elk-3 Contributes to the Progression of Liver Fibrosis by Regulating the Epithelial-Mesenchymal Transition

Abstract: Background/AimsThe role of Elk-3 in the epithelial-mesenchymal transition (EMT) during liver fibrogenesis remains unclear. Here, we determined the expression of Elk-3 in in vitro and in vivo models and in human liver fibrotic tissues. We also investigated the molecular relationships among Elk-3, early growth response-1 (Egr-1), and the mitogen activated protein kinases (MAPK) pathway during EMT in hepatocytes.MethodsWe established anin vitro EMT model in which normal mouse hepatocyte cell lines were treated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 40 publications
0
28
0
Order By: Relevance
“…Mutations in ELK3 disrupt vasculogenesis, angiogenesis and wound healing in mice during development and in adulthood (24,25). In addition, our previous study demonstrated that ELK3 contributes to epithelial-mesenchymal transition (EMT) of mouse hepatocytes by regulating egr-1 (26). EMT, a process whereby epithelial cells reduce their intercellular adhesions and gain mesenchymal properties, is a critical event in the process of cancer invasion and metastasis (27,28).…”
Section: Elk3 Promotes the Migration And Invasion Of Liver Cancer Stementioning
confidence: 99%
See 1 more Smart Citation
“…Mutations in ELK3 disrupt vasculogenesis, angiogenesis and wound healing in mice during development and in adulthood (24,25). In addition, our previous study demonstrated that ELK3 contributes to epithelial-mesenchymal transition (EMT) of mouse hepatocytes by regulating egr-1 (26). EMT, a process whereby epithelial cells reduce their intercellular adhesions and gain mesenchymal properties, is a critical event in the process of cancer invasion and metastasis (27,28).…”
Section: Elk3 Promotes the Migration And Invasion Of Liver Cancer Stementioning
confidence: 99%
“…In a previous study, we demonstrated that ELK3 expression plays an important role in the process of EMT during liver fibrogenesis (26). Acquiring cell motility is necessary for the transition from an epithelial to a mesenchymal phenotype (27,28).…”
Section: Elk3 Expression Is Elevated In Cd133mentioning
confidence: 99%
“…Li et al 8. investigated novel molecular mechanisms involved in the EMT of hepatocytes and liver fibrosis.…”
mentioning
confidence: 99%
“…However, to the best of our knowledge, there have not been any studies investigating the role of Elk-3 and Egr-1 during EMT of hepatocyte in liver fibrosis. Li et al 8. demonstrated that the expression levels of Elk-3 and Egr-1 were significantly increased during TGF-β1-induced EMT of hepatocytes, in both the CCl 4 -induced mouse liver fibrotic tissues and in the human liver cirrhotic tissues.…”
mentioning
confidence: 99%
See 1 more Smart Citation